Freedom, Equality – and Event? Criticising and deepening theories of “radical democracy” - Lehner, Daniel (Momentum Quarterly, 2012)
The European protests against austerity policies, the occupy-movement in the USA and the revolts of the „arab spring“ have all raised the question about democracy, its actual deficits but also its future possibilities. Against this empirical background of problematising democracy this theoretical article introduces some approaches and figures that can all be attributed to theories of radical democracy. These neomarxist and poststructuralist theories reject the western-liberal identification of democracy with periodic votes, constitutional legality and market economy. Democracy would not be a form of government but rather a practical and collective struggle for the extension and universalisation of the “democratic promise” of freedom and equality for all people – including also the field of economy. This article captures this emancipatory point of view and argues for a concept of democratising practices which can also emerge in the form of singular, political events every now and then.